The viability of self-employment for individuals with disabilities in the United States: A synthesis of the empirical-research literature. - Yamamoto, Scott; Unruh, Deanne; Bullis, Michael (Journal of Vocational Rehabilitation, 2012)
The lack of employment opportunities and stable employment for individuals with disabilities continues to pose personal and societal difficulties and challenges. Moreover, research and government statistics have consistently reported that individuals with disabilities have lower employment wages and benefits than individuals without disabilities, as well as limited opportunities for promotion and career advancement. Not surprisingly, individuals with disabilities also experience persistently higher poverty rates. While much is known in the empirical-research literature about individuals with disabilities who work for someone else, much less is known about individuals in self-employment. Some anecdotal information suggests that self-employment may be a way to improve these outcomes. In the present paper, we reviewed, analyzed, and synthesized the findings of empirical-research studies on self-employment of individuals with disabilities in the United States. We found that successful self-employment is defined in financial and non-financial terms and is largely influenced by three factors: individual characteristics, level of supports, and accountability systems. Because of the small number of U.S. research studies on self-employment, however, our conclusions are tentative. Further empirical research is needed, focusing especially on long-term outcomes. Implications for researchers, individuals with disabilities, and other stakeholders are discussed in conclusion.